Between Lesson Planning And Classroom Implementation: A Systematic Literature Review - Ibriza, Falihatul; Ningsih, Nurma Mutiara (Peneliti.net, 2025)
This research conducts a systematic literature review (SLR) to examine how lesson planning aligns with its actual implementation in classroom environments, with a particular focus on English as a Foreign Language (EFL) Settings. Although lesson planning is widely recognized as essential for effective teaching, numerous studies reveal ongoing difficulties in translating plans into practice, often due to institutional limitations, unexpected classroom situations, and mismatches in pedagogical approaches. Drawing upon Constructivist Learning Theory and the framework of Pedagogical Content Knowledge (PCK), this review synthesizes evidence from 24 peer-reviewed empirical studies, all selected using a rigorous protocol based on the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The analysis identifies four central themes: factors contributing to gaps between planning and execution, strategies teachers employ to bridge these gaps, the importance of reflective practice, and the impact of contextual and institutional influences. Employing the PRISMA framework strengthens the transparency, reproducibility, and methodological rigor of the review. The findings offer actionable recommendations for educators, policymakers, and curriculum designers, emphasizing the importance of integrating flexible, reflective, and context-sensitive planning approaches that can respond effectively to the shifting needs of students and the realities of classroom instruction.